A review of structural patterns and melting processes in the Archean craton of West Greenland: Evidence for crustal growth at convergent plate margins as opposed to non-uniformitarian models - Polat, Ali (Tectonophysics, 2015)
The Archean craton of West Greenland consists of many fault-bounded Eoarchean to Neoarchean tectonic terranes (crustal blocks). These tectonic terranes are composed mainly of tonalite-trondhjemite-granodiorite (TTG) gneisses, granitic gneisses, metavolcanic-dominated supracrustal belts, layered anorthositic complexes, and late- to post-tectonic granites. Rock assemblages and geochemical signatures in these terranes suggest that they represent fragments of dismembered oceanic island arcs, consisting mainly of TTG plutons, tholeiitic to calc-alkaline basalts, boninites, picrites, and cumulate layers of ultramafic rocks, gabbros, leucogabbros and anorthosites, with minor sedimentary rocks. The structural characteristics of the terrane boundaries are consistent with the assembly of these island arcs through modern style of horizontal tectonics, suggesting that the Archean craton of West Greenland grew at convergent plate margins. Several supracrustal belts that occur at or near the terrane boundaries are interpreted as relict accretionary prisms. The terranes display fold and thrust structures and contain numerous 10 cm to 20 m wide bifurcating, ductile shear zones that are characterized by a variety of structures including transposed and redistributed isoclinal folds. Geometrically these structures are similar to those occurring on regional scales, suggesting that the Archean craton of West Greenland can be interpreted as a continental scale accretionary complex, such as the Paleozoic Altaids. Melting of metavolcanic rocks during tectonic thickening in the arcs played an important role in the generation of TTGs. Non-uniformitarian models proposed for the origin of Archean terranes have no analogs in the geologic record and are inconsistent with structural, lithological, petrological and geochemical data collected from Archean terranes over the last four decades. The style of deformation and generation of felsic rocks on outcrop scales in the Archean craton of West Greenland and the Mesozoic Sulu orogenic belt of ...